Aviation induced diurnal North Atlantic cirrus cover cycle - Graf, Kaspar; Schumann, Ulrich; Mannstein, Herrmann; Mayer, Bernhard (Geophysical Research Letters, 2012)
Aviation induced cirrus (AIC) cover is identified from mean diurnal cycles of cirrus cover and air traffic density in the North Atlantic flight corridor. Traffic data for this region show an aviation Ã¢ÂÂfingerprintÃ¢ÂÂ with two maxima during morning eastbound and afternoon westbound traffic. The same aviation fingerprint is found in cirrus cover. Cycle differences between west and east domain parts allow separating between aviation and natural diurnal changes. Cirrus cover is derived from 8 years of Meteosat infrared data. Linear contrail cover is estimated from the same data. Background cirrus without aviation impact is estimated from cirrus observations over the South Atlantic and from numerical weather prediction forecast. The cirrus cover cycle is well approximated by linear response to traffic density with fitted delay times of 2.3Ã¢ÂÂ4.1 h, implying AIC cover of 1Ã¢ÂÂ2%, more than expected from recent models.